2011
DOI: 10.1016/j.rmed.2011.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Inhaler technique and asthma: Feasability and acceptability of training by pharmacists

Abstract: Poor inhaler technique is frequent in asthma, but its long-term consequences have been seldom assessed. Pharmacists are ideally positioned to teach inhaler technique. This prospective observational study evaluated the feasibility of inhaler training by pharmacists in patients receiving inhaled corticosteroids by pressurised metered-dose inhaler (pMDI) or breath-actuated MDI. In parallel, the relationships between inhaler technique, adherence, and asthma control, and their modulation one month after training we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
210
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(222 citation statements)
references
References 24 publications
9
210
1
2
Order By: Relevance
“…Correlation of ACQ with functional parameters related to asthma in children has also been demonstrated in six minute walking test in a previous study (35). Some authors reported that patients who use their inhalation device correctly have better asthma control (3,5,8,11,36). McWhirter et al, Horner and Brown showed that children with asthma have lower requirement for medication, reduction in symptoms of wheeze and improvement in children's quality of life as their inhaler skill improved (14,15).…”
Section: Resultsmentioning
confidence: 99%
“…Correlation of ACQ with functional parameters related to asthma in children has also been demonstrated in six minute walking test in a previous study (35). Some authors reported that patients who use their inhalation device correctly have better asthma control (3,5,8,11,36). McWhirter et al, Horner and Brown showed that children with asthma have lower requirement for medication, reduction in symptoms of wheeze and improvement in children's quality of life as their inhaler skill improved (14,15).…”
Section: Resultsmentioning
confidence: 99%
“…Globally, the centrality of inhaler technique maintenance in asthma management is heavily emphasised by numerous respiratory authorities, and referred to more than 50 times in key asthma management documents [1]. However, although healthcare professional-coordinated inhaler technique training can improve asthma control [2,3], inhaler technique remains a significant problem. From the currently available data, across all ages, as many as 90% of patients are estimated to demonstrate incorrect technique [4], contributing to increased hospitalisations [5] and forfeiture of billions of dollars in pharmaceutical expenditure [6].…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] As a consequence, the role of education from trained caregivers is important to reduce poor inhaler technique not only at the time of the first prescription but also at follow-up visits. 8,9 Many studies have evaluated the time required for educating naive adult users to inhaler mastery, [10][11][12][13][14][15][16][17] but, to our knowledge, no information is available to evaluate the re-education time required to achieve inhaler mastery in experienced users with faulty baseline technique. Our previous study, the GENEBI Project 2 , investigated home inhaler practice among experienced stable subjects with chronic obstructive airway diseases referred to chest clinics throughout Italy.…”
Section: Introductionmentioning
confidence: 99%